Hubungan Beban Kerja dengan Burnout Perawat Rumah Sakit Islam Ibnu Sina Bukittinggi - Muhammad Reza Mahendra; Zulfa Zulfa; Elsa Luvia Harmen (Inovasi Kesehatan Global, 2026)
Nurse workload is the total number or volume of tasks that must be completed by nurses during their professional practice in hospitals, including both physical and mental responsibilities in providing nursing care to patients. Meanwhile, nurse burnout is a condition of emotional and mental fatigue experienced by nurses due to prolonged work pressure and the high intensity of emotional demands in the hospital environment. However, workload problems are still commonly found in hospitals, with one of the main contributing factors being work stress caused by excessive job demands and continuous pressure during work activities. The population in this study were outpatient, inpatient and emergency nurses at Ibnu Sina Islamic Hospital, Bukittinggi in 2025 This study used a quantitative method with a cross-sectional approach, analyzing the relationship between one variable and another. This study had 130 samples consisting of outpatient nurses, inpatient nurses, and emergency room nurses. Sampling was carried out using a total sampling technique. The results of this study indicate a significant relationship between workload and burnout at a significance level of 0.00 (≤ 0.05). There is a significant relationship between workload and nurse fatigue at Ibnu Sina Islamic Hospital Bukittinggi in 2025.